The role and therapeutic potential of glucose metabolism in multidrug resistance of cancer - Wang, Qijing; Li, Kai; Li, Liang; Li, Qin; Qi, Yanyu; Liu, Kai; Yuan, Hang; Lin, Ping (Frontiers in Cell and Developmental Biology, 2025)
Cancer represents a serious threat to human health and life. Despite recent advances in the cancer therapy that significantly extend patient survival, many individuals still undergo drug resistance, even to multiple chemotherapeutic drugs, known as multidrug resistance (MDR). MDR causes the treatment failure and promotes the risk of tumor recurrence and metastasis, which has been a critical clinical challenge. The molecular mechanisms for cancer cells developing MDR are complex and largely unclarified. ATP-binding cassette (ABC) transporters-mediated enhanced drug efflux and glucose metabolic reprogramming have been recently identified as key factors that limit drug efficacy. In addition to regulating glucose metabolism, several glycolytic enzymes exhibit aberrant cellular localization, including translocation to the nucleus, cell membrane or mitochondria, which imparts their non-classical pro-oncogenic functions to facilitate tumor progression and MDR. In this review, we summarize the roles and molecular insights of glycometabolic enzymes in MDR progression and discuss existing therapeutic strategies of targeting glucose metabolic enzymes for overcoming MDR.